A noção de sistema na fundação da linguística moderna - Coelho, Micaela Pafume (2015)
This work is intended to investigate the saussurian notion of system. Such a notion is fundamental to Ferdinand de Saussure's theorization, since it composes the definition of "langue", as he thought it. This definition was crucial to the delimitation of linguistics' specific object of study, which granted its place among modern sciences. However, the notion of system was not created by Saussure. Not only in Linguistics, but also in other areas, this notion appeared in very ancient studies, mingling with the establishment of man in society and the development of their economic and organizational activities. Specifically, in the context of language studies, the system consists in a notion that composed the work of the first grammarians in the West, in ancient Greece. Moreover, this notion was also used afterwards, in the synonymy studies and in the comparative analysis of languages, developed by scholars of the nineteenth century. Nevertheless, although Saussure had had his formation in Leipzig and Berlim, amid comparatists studies, his notion of system is an innovation, while is also continuing. In light of this, we aim to highlight the aspects of the saussurian notion of system that allow the establishment of a relationship of continuity and rupture with other conceptions of system. For that, we will investigate four Saussure authored documents: the « Cours de linguistique générale », the « Mémoire sur le système primitif des voyelles dans les langues indo-européennes », and the two sets of manuscripts « De l'essence double du langage » and « Notes pour le cours III ».